SAYAT NOVA AND THE ARMENIAN ASHUGH ART - Harutyunyan H. H.; Asatryan A. H.; Khachatryan D. K. (International Journal of Innovative Technologies in Social Science, 2021)
The article is dedicated to the problems of the creative heritage of the famous Armenian troubadour Sayat Nova. The poetic legacy of this great singer of man, love, beauty and justice is one of the most striking revelations of the Armenian (and not only Armenian) creative genius. Thanks to its universal human character, nationality, social richness and unique poetic art, the word Sayat-Nova still sounds today with the same force, in tune with the most intimate feelings of the human soul. The popularity of Sayat-Nova’s poetry, in particular among the peoples of the Caucasus, is absolutely exceptional. Sayat-Nova is an outstanding musician-inventor and there is a regular need to reflect on new developments in the study of his song heritage.